"ANALYZING THE ECONOMIC VALUATION OF RECYCLED WATER" - Genu (Ajay) Ramkisan Darekar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In some parts of the world, water reuse has been driven as an alternate water supply through considerations such as water shortages in arid and semi-arid regions, water security concerns in areas where water demand exceeds water availability, and rigorous and costly requirements for removing nutrients and contaminants from effluent release into surface water. This study has verified the success of measures of productivity, effectiveness and dependability for the determination of scheme performance throughout the different life cycle phases.